2017
DOI: 10.1016/j.jnucmat.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

He+ irradiation induced cracking and exfoliating on the surface of Ti3AlC2

Abstract: We report a systematic study of the effects of a 400 keV helium ion beam irradiation on the surface morphology and crystal structure of Ti 3 AlC 2 by combined scanning electron microscopy, grazing incidence X-ray diffraction and transmission electron microscopy. Helium irradiation experiments were performed at both room temperature and 500 o C, respectively, with fluence up to 2.0 × 10 17 He + /cm 2. After irradiation, intragranular orientated cracks grew along the (10 1 0) Ti3AlC2 plane and the surface has st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…This irradiation-induced phase transformation from hcp-Mn+1AXn to fcc-(Mn+1A)Xn has been confirmed with He and Au irradiations performed on Ti3AlC2, Ti2AlC, Ti3SiC2, Nb4AlC3, V2AlC, Ti4AlN3, and Ti2AlN MAX phases [31]. Cracks may form during RT irradiations due to lattice distortions, i.e., a contraction along the <a> axis and an expansion along the <c> axis, which are minimized during irradiation at elevated temperatures [9,15,18,30]. Cracks were reported to nucleate at string-like and plate-like He bubbles [9,30].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…This irradiation-induced phase transformation from hcp-Mn+1AXn to fcc-(Mn+1A)Xn has been confirmed with He and Au irradiations performed on Ti3AlC2, Ti2AlC, Ti3SiC2, Nb4AlC3, V2AlC, Ti4AlN3, and Ti2AlN MAX phases [31]. Cracks may form during RT irradiations due to lattice distortions, i.e., a contraction along the <a> axis and an expansion along the <c> axis, which are minimized during irradiation at elevated temperatures [9,15,18,30]. Cracks were reported to nucleate at string-like and plate-like He bubbles [9,30].…”
Section: Introductionmentioning
confidence: 55%
“…The MAX phases are steadily gaining attention for select envisaged nuclear applications, and a number of He irradiation studies on the MAX phases have already been reported in the open literature -for example on Ti3AlC2 [5,[9][10][11][12][13][14][15][16], Ti2AlC [17][18][19], Ti3SiC2 [6,[20][21][22], Cr2AlC [23,24], V2AlC [25], and Ti4AlN3 [19]. Overall, the He irradiation of MAX phase compounds tends to result in He atoms residing preferentially in the A-layer, thereby dislocating A-elements from their original sites [6,10,12,13,18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…1) The experimental temperature was controlled at 500 °C. Samples were taken every 500 h. The oxygen concentration in the liquid LBE is saturated and it was calculated to be 6.3×10 -4 wt.% using the following equation [14]:…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the authors of Refs. [21][22][23] observed the morphology of He bubbles in He-irradiated Ti 2 AlC and Ti 3 AlC 2 by bright-field transmission electron microscopy (TEM). However, due to the limitation of the resolution, the clear shapes of the He bubbles and their positions in the lattice could not be clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…The darker spots are Al 3 O 2 , which was introduced by Al doping during the sample fabrication using the reactive sintering method. Unlike Ti 3 AlC 2 and Ti 2 AlC, which show a high density of cracks after RT irradiation[9,23,24], the surface of Ti 3 SiC 2 is free of cracks at both RT and 750 ℃, suggesting that Ti 3 SiC 2 has a better resistance to irradiation-induced surface cracks.In order to analyze the morphology and the distribution of He bubbles as well as to analyze the irradiated Ti 3 SiC 2 in TEM, bright field TEM images of the Ti 3 SiC 2 after irradiation at RT…”
mentioning
confidence: 98%